DIFUSI INOVASI PEMBELAJARAN BERMAKNA DI SDN CIJANTUNG 02 - Latip, Asep Ediana; Maharani, Adinda; Salsabilla, Silvy Kumalasari (JURNAL EDUCATION AND DEVELOPMENT, 2025)
This study aims to analyze the implementation of meaningful learning at SDN Cijantung 02 through an innovation diffusion approach. Meaningful learning is considered crucial in improving the quality of education, especially in the digital era. The method used is quantitative with a survey approach, where a questionnaire was distributed to four teachers as respondents. The results show that most teachers understand and support the implementation of meaningful learning, although there are challenges in planning and time constraints. Meaningful learning has been shown to enhance student comprehension and active participation in class. The support of the school principal and collaboration among teachers also facilitates the implementation of this innovation. However, limitations in facilities and parental support pose challenges that need to be addressed. This study provides recommendations for intensive training and improved facilities to better support the implementation of meaningful learning.